A well-founded fear : the congressional battle to save political Asylum in America - Schrag, Philip G., 1943- (Routledge, 2000)
A fascinating case study of the legislative process and the author's experiences as a public interest lobbyist, Schrag tells how a coalition of human rights and refugee groups fought to preserve the rights of refugees and asylum seekers.